2017
DOI: 10.1111/jgs.15108
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Reported Function More Informative than Frailty Phenotype in Predicting Adverse Postoperative Course in Older Adults

Abstract: Background Current preoperative assessment tools such as the American College of Surgeons Surgical Risk Calculator (ACS Calculator) are suboptimal for evaluating older adults. Objective To evaluate and compare the performance of the ACS Calculator for predicting risk of serious postoperative complications, with the addition of self-reported physical function versus a frailty score. Design Prospective cohort. Setting Two tertiary care academic medical centers in Massachusetts. Participants 403 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Our analysis combines use of both anchor-and distribution-based techniques for determining the MCID, which strengthens the confidence in our estimates of meaningful increments of change that are both perceptible to patients and above measurement error. Our findings add to the growing body of evidence supporting the psychometric properties of the LLFDI-FC (1,5,7,13) and its usefulness as a patient-reported measure of function for older adults.…”
Section: Discussionsupporting
confidence: 59%
“…Our analysis combines use of both anchor-and distribution-based techniques for determining the MCID, which strengthens the confidence in our estimates of meaningful increments of change that are both perceptible to patients and above measurement error. Our findings add to the growing body of evidence supporting the psychometric properties of the LLFDI-FC (1,5,7,13) and its usefulness as a patient-reported measure of function for older adults.…”
Section: Discussionsupporting
confidence: 59%
“…Many investigators report significant associations between measures of frailty and postoperative complications, 1,5,6,8,16,19,20,29,[36][37][38][39][40] but only some report C statistics, 6,29,30,33,36,37,39 which quantify clinical importance. Reported C statistics range from 0.53 to 0.68, with most being between 0.60 and 0.65, 6,29,30,39 which are similar to our findings. A statistically significant odds ratio 34,35 does not imply predictive ability or discriminative classification, making measures of discrimination such as the C statistic critical.…”
Section: Discussionmentioning
confidence: 99%
“…6,36 Additionally, the Fried Index, which is the basis for the Hopkins Frailty Score, has been validated in a perioperative setting. 18,21 Recently, Kapoor et al 39 compared the Fried Index with the self-reported Late Life Function and Disability Instrument and found them to be comparable in perioperative settings. It thus seems unlikely that our results would much differ had we selected other measures of frailty.…”
Section: Preoperative Frailty Assessmentmentioning
confidence: 99%
“…The Risk Analysis Index has been found to be a helpful adjunct in addition to the ACS score because of its ability to leverage patient frailty as an identifier for potential surgical prehabilitation [ 25 ]. Furthermore, use of a self-identified functionality scale was a better predictive tool for adverse outcomes when combined with the ACS calculator than the frailty phenotype [ 26 ].…”
Section: Discussionmentioning
confidence: 99%